1991
DOI: 10.1093/infdis/164.5.1007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Cysticercosis Enzyme-Linked Immunoelectrotransfer Blot in Patients with Neurocysticercosis

Abstract: During the 3 years that the enzyme-linked immunoelectrotransfer blot (EITB) assay for the diagnosis of human cysticercosis has been in use at the Centers for Disease Control, 50 patients with both pathologically confirmed neurocysticercosis and computed tomographic (CT) or magnetic resonance imaging (MRI) scan results were identified. Of 32 patients with two or more lesions, 94% had detectable antibodies by EITB compared with 28% of 18 patients with single lesions. Patients with only calcified cysts (single or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
135
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(145 citation statements)
references
References 7 publications
3
135
1
6
Order By: Relevance
“…These results suggest a higher sensitivity of the Tcra antigen in the detection of serum antibodies in patients that do not present signs of inflammatory processes. Some authors have reported lower sensitivity of the immunological tests in patients with calcified cysts, independent of the antigen employed 24,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a higher sensitivity of the Tcra antigen in the detection of serum antibodies in patients that do not present signs of inflammatory processes. Some authors have reported lower sensitivity of the immunological tests in patients with calcified cysts, independent of the antigen employed 24,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Serological examinations such as ELISA and enzyme-linked immunoelectrotransfer blot (EITB) provide high sensitivity for neurocysticercosis. 1,3,11,12) However, these methods are not sensitive for cysticercosis with a solitary lesion. 12,14) The positive finding for CSF examination by EITB is less than 40% in cases of solitary neurocysticercosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,11,12) However, these methods are not sensitive for cysticercosis with a solitary lesion. 12,14) The positive finding for CSF examination by EITB is less than 40% in cases of solitary neurocysticercosis. 12) Mitochondrial DNA analysis is useful for routine identification of taeniid cestodes and particularly for correlating the pathogenicity and genotypes of T. solium if parasite materials are available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations